The Impact of Microfinance on Poverty Reduction in Egypt: An Empirical Study - El Hadidi, Hala (The Arab Journal of Administration, 2020)
Microfinance became a critical aspect in the credit markets as an effective tool for poverty reduction and socioeconomic-development. Yet, the impact still questioned and varies from one country to another and from urban to rural areas. The aim of this paper is to examine the role of Egyptian microfinance on household income. A cross-sectional survey interviewed 780 from old and new clients in Greater Cairo and rural areas in Egypt. The stratified random method was used to collect the data from urban and rural districts. The finding of multinomial logistic reveals that Microfinance has positive impact on household income of women borrowers who spent three years in the scheme as compared to new borrowers who have not received treatment.